2013
DOI: 10.1159/000346112
|View full text |Cite
|
Sign up to set email alerts
|

Influence of IL-1RN Intron 2 Variable Number of Tandem Repeats (VNTR) Polymorphism on Bipolar Disorder

Abstract: Background/Aims: Several lines of evidence point to the role of neurobiological mechanisms and genetic background in bipolar disorder (BD). The interleukin-1 receptor antagonist (IL-1Ra) is the principal regulator of IL-1α and IL-1β bioactivities. This study aimed to investigate the potential role of the variable number of tandem repeats (VNTR) polymorphisms of the IL-1Ra gene (IL1RN) in conferring susceptibility to BD. Methods: In total, 217 patients meeting DSM-IV-TR criteria for BD and 212 controls were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…8). All these validated genes have been suggested to play important roles in the CNS and neurological disorders [23, 4853]. Our validation by PCR confirmed that the Meth treatment has the capacity to directly stimulate the upregulation of these genes, which have an involvement in inflammatory processes in the brain.…”
Section: Resultssupporting
confidence: 67%
“…8). All these validated genes have been suggested to play important roles in the CNS and neurological disorders [23, 4853]. Our validation by PCR confirmed that the Meth treatment has the capacity to directly stimulate the upregulation of these genes, which have an involvement in inflammatory processes in the brain.…”
Section: Resultssupporting
confidence: 67%
“…In the same locus, another study in the Iranian population on the À511 C>T (rs16944) polymorphism found that the T allele carrier state is associated with BD (71), an allele previously linked with longer episodes and total brain and more specifically left dorsolateral prefrontal cortex grey matter deficits when compared to the non-T allele carrier counterparts (71,77). Although two other studies regarding the same VNTR (variable number tandem repeat) of 86 bp in length in intron 2 of the IL1RN gene (interleukin-1 receptor antagonist) did not confirm this association in the Korean and Iranian populations, Rafiei et al, in a Iranian sample, after having stratified BD patients into two subgroups according to age at onset, found that presence of the allele containing two repeats was associated with later onset (71,76,78,79). This allele is associated with more prolonged and severe proinflammatory immune responses (80).…”
Section: Modulators Of Clinical Presentationmentioning
confidence: 97%
“…Genetic studies with bipolar patients have shown that they have alterations in their TNF-α gene, which has been related to higher levels of TNF-α production [25,26]. In addition, it was demonstrated that there is a genetic variant of the IL-1 and RIL-1 genes in BD [27,28]. It was also discovered that there is mRNA overexpression of TNF-, IL-1훽, IL-6, and CCL2 in the monocytes of bipolar patients and also in the offspring of bipolar parents [29].…”
Section: Introductionmentioning
confidence: 99%